Conservación y valor nutritivo del contenido ruminal para la alimentación de cerdos (1990)
The experiment was carried out at the Animal Nutrition and swine sections of the national Agriculture Research Center of Tibaitata, with the purpose of determining the nutritive value, conservation system and proper way of utilization of ruminal content. Mixtures of ruminal content along with ground sorghum were made at levels of 20-40-60-80 and 100, evaluating its nutritive value at fresh state and at fourteen and twenty eight days of storage. Mixtures with 60, 40 and 20% of ruminal content at 14 and 28 days of storage showed organoleptic charactheristics of good silage, with a pH value between 4.1 and 4.8 dry matter content varied between 8.0 and 75.1% according to the level of the ruminal content of the mixture; a favorable effect in the total protein level of 26.3% was observed when the ruminal content sorghum mixtures were subject to conservations. The same happened to fat. Storage time and treatments decreased in 38.8% fibre percentaje due to the action of those microorganism capable of degrading cellulose. The mixture of 40% ruminal content and 60% ground sorghum, ensued during 14 days, significantly improved (P(0.01) dry matter digestibility, protein, nitrogen free extract and energy when compared to fresh mixture. Therefore, this ensilded mixture is recommended for feeding pigs, because of its high digestibility and good energy content.